2018
DOI: 10.1016/j.heliyon.2018.e00930
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to the application of hexagonal mesoporous silica in solid-phase extraction of drugs

Abstract: Mesoporous silica with hexagonal type structure containing amine functional group was introduced. Firstly, aminopropyl hexagonal mesoporous silica was synthetized in a co-condensation process, via templating route of n-dodecylamine. Then synthesized mesoporous material were characterized, and FT-IR spectrum confirmed the presence of amine group and CHN analysis determined the amount of organic layer. The high surface area (750 m2/g) was determined by applying nitrogen adsorption-desorption technique. The morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The effects of MS on a wide range xenobiotics, namely heavy metals, acetaminophen, phenobarbital, and iron and copper overload has been successfully tested by our research team. 18 , 52 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of MS on a wide range xenobiotics, namely heavy metals, acetaminophen, phenobarbital, and iron and copper overload has been successfully tested by our research team. 18 , 52 …”
Section: Discussionmentioning
confidence: 99%
“…The effects of MS on a wide range xenobiotics, namely heavy metals, acetaminophen, phenobarbital, and iron and copper overload has been successfully tested by our research team. 18,52 The current investigation was designed to synthesize a functionalized MS for ammonium ion adsorption in vitro and alleviating HE as a severe clinical complication in an animal model. We found that MS has mainly remained in the GI (Figure 8).…”
mentioning
confidence: 99%
“…Another possible way of utilization is the formation of specific systems for drug delivery [19]. Otherwise, the HCP structures have found a great use in macro-, micro-, and nano-applications in electronics [20], electro-optics [21,22], bioanalytics [23], or in nanofabrication [24].…”
Section: Introductionmentioning
confidence: 99%
“…To address these questions, we have studied three models of functionalized mesoporous silica particles (MS-NH 2 , MS-3NH 2 , and MS-chitosan), varying according to their electrostatic and hydrophobic moieties, on fibrillation of human insulin. Of all the mesoporous materials (particles having a uniform pore size between 2 and 50 nm), mesoporous silica particles, due to their uniform pore size, highly ordered structure, and functionalizability, are of particular interest in industrial and academic communities as drug delivery systems. Currently, new applications of these particles are being introduced. , …”
Section: Introductionmentioning
confidence: 99%